Barriers and facilitators to provide continuity of care to dischargeable patients in disasters: A qualitative study. Issue 4 (April 2019) - Feizolahzadeh, Sima; Vaezi, Aliakbar; Mirzaei, Masoud; Khankeh, Hamidreza; Taheriniya, Ali; Vafaeenasab, Mohammadreza; Khorasani-Zavareh, Davoud
Highlights: In most disaster preparedness plans, the health problems of hospitalized patients who are early discharged due to hospital surge capacity are disregarded. Discontinuity of care can affect health and increase in the mortality of the discharged patients, due to interruption of the treatment, particularly in disaster situations that may lead to infrastructure destruction and lack of access to health care. In this study, the authors explored challenges and facilitators to provide continuity of care to these patients after leaving hospitals with all involved stakeholders, employing qualitative study in order to have a comprehensive approach. Abstract: Objective: Early discharge of some in-patients is the effective measure to create hospital surge capacity in disasters. However, some of these patients may need to post-discharge continuity of care. The aim of the current study then is to explore the barriers of continuity of care, and to provide suitable solutions for potentially dischargeable patients during disasters. Methods: This qualitative study was conducted in Iran in 2017. The data was collected via unstructured interviews with 24 disaster professionals; and analyzed by content analysis method. Results: Identified barriers to the continuity of care were classified into seven categories, 'lack of disaster paradigm'; 'challenges of pre-hospital system'; 'insufficient coordination and cooperation'; 'inadequate hospital preparedness'; 'lack of using available resources and capacities'; 'poor patients' knowledge' and 'poor planning'. The suggested solutions for post-discharge continuity of care were: creation of registry and follow-up system; removing pre-hospital challenges; including disaster management courses in medical school curriculum; promoting hospital preparedness by All-Hazard Approach; and effective use of available resources. Conclusion: Understanding the barriers to continuity of care for discharged patients for adopting policies based on experiences of health care providers can help planners to design and implement effective programs, which will enhance patients' access to necessary care.